Counseling Of Fluorosis, Utilization, And Clearance Of Fluor In Water, Desa Mojosari Kecamatan Asembagus Kecamatan Situbondo - Suproborini, Arum -; Laksana, Mochamad Soeprijadi Djoko; Yudiantoro, Dwi Fitri; Ikhsan, Ismail Da'imul (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
Dental fluorosis is a disorder of mottled or mottled enamel structure as a result of excess fluoride intake during tooth formation. Water is one source of fluorine. The purpose of this community service is to assist the community in improving dental health and preventing dental and bone fluorosis. The implementation of this community service uses lecture and discussion methods. The stages of this service include pretest, delivery of material, post test, and discussion sessions. Post test results show an increase in community knowledge. It is hoped that this increase in knowledge can be applied by the Mojosari village community in an effort to procure water to meet their needs. Keywords: fluorosis, fluorosis, Mojosari village